Saturday
March 25, 2017

Post a New Question

Posted by on .

integrate the following
(3y-7x-3)dx+(7y-3x-7)dy=0

  • calculus - ,

    rearrange things a it to get

    (3y-7x-3)+(7y-3x-7)y'=0
    now integrate term by term
    3xy-7/2x^2-3x + 7/2y^2-3xy-7y=0

    the 3xy's go away; multiply by 2/7 to get

    -(x^2+6/7)+(y^2-2y) = 0
    -(x+3/7)^2+(y-1)^2 = 58/49

    an hyperbola opening up and down

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question